PELAKSANAAN PENANGGUHAN PENAHANAN TANPA JAMINAN UANG ATAU ORANG DALAM PROSES PEMERIKSAAN PERKARA PIDANA PADA TINGKAT PENYIDIKAN DI DIREKTORAT RESERSE KRIMINAL UMUM - Arara, Desfita; ', Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Suspension of detention is release the suspect or defendant from detention before detention time limit expires. In article 31 of KUHAP suspension of detention can be done without bail or person. But, in practice rarely there detention without bail or person. Releated issues suspension detention regulated in article 31 KUHAP, there are two points to be conclude: First, implementation of suspension of detention without bail or person at Direktorat Reserse Kriminal Umum Kepolisian Daerah Riau do if there is a request from suspect or dependant, request of suspension of detention approved by the investigator or public prosecutor or judges who are hold with or without bail or person be like set there are agreement from suspect or defendant who are holded to abide by the terms and bail set. Second, character of Direktorat Reserse Kriminal Umum Kepolisian Daerah Riau in giving suspension of detention can be seen investigation’s appropriate level, classification of case and the reason from the suspect or dependant ask for suspension of detention.Keywords: implementation – suspension of detention